2020
DOI: 10.1002/kjm2.12209
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ubiquitin‐specific peptidase 13 inhibits cell growth of hepatocellular carcinoma by reducing c‐Myc expression

Abstract: Ubiquitin‐specific peptidase 13 (USP13) has been reported to be involved in the tumorigenesis of several tumors, but its function in tumors is still controversial. In this study, the function of USP13 in hepatocellular carcinoma (HCC) was investigated, and we found that USP13 was significantly upregulated in both of primary HCC tumor tissues and cell lines. And HCC patients with high USP13 expression had a shorter overall survival or relapse‐free survival than patients with low USP13 expression. In HCC cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In accordance with the data in cases at different grades, USP39 displayed a dynamic increasing from pre-HCC status to HCC. However, USP13, USP22, and USP39, previously correlated with the malignant phenotypes of HCC cells (26)(27)(28), showed less differences among the sub-groups. It could be speculated that these USPs might be not key driver genes for HCC progression though they enhance aggressive behaviors of HCC cells.…”
Section: Discussionmentioning
confidence: 76%
“…In accordance with the data in cases at different grades, USP39 displayed a dynamic increasing from pre-HCC status to HCC. However, USP13, USP22, and USP39, previously correlated with the malignant phenotypes of HCC cells (26)(27)(28), showed less differences among the sub-groups. It could be speculated that these USPs might be not key driver genes for HCC progression though they enhance aggressive behaviors of HCC cells.…”
Section: Discussionmentioning
confidence: 76%
“…Ubiquitin specific protease 13 (USP13), which belongs to the deubiquitinating enzymes (DUBs) superfamily, is implicated in the occurrence and progression of human cancer via promoting deubiquitination and stabilization of substrate proteins, including myeloid cell leukemia 1 (MCL1) (Zhang et al, 2018), phosphatase and tensin homolog (PTEN) (Zhang et al, 2013), melanocyte inducing transcription factor (MITF) (Zhao et al, 2011), Myc (Fang et al, 2017), USP10 (Liu et al, 2011), and RAP80 (Li et al, 2017). A recent study presents that USP13 silencing represses HCC growth possibly by decreasing Myc expression (Huang et al, 2020). Nevertheless, whether USP13 contributes to HCC progression by regulating the toll-like receptor 4/myeloid differentiation primary response gene 88/nuclear factor-κB (TLR4/MyD88/NF-κB) pathway remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The c-Myc gene encodes a proto-oncoprotein, a widely recognized transcription factor regulating approximately 10–15% of genes implicated in cell proliferation, differentiation, apoptosis and other processes ( Friedman et al, 2017 ; Habib et al, 2020 ), and c-Myc mutations are often associated with tumors ( Berns et al, 1997 ; Brodsky and McCracken, 1999 ; Hermeking et al, 2000 ; Morrish et al, 2003 ; Wilson et al, 2004 ). Recently, it has been reported that USP13 is co-overexpressed with c-Myc in many tumors, such as NSCLC ( Wu et al, 2019 ), cholangiocarcinoma (CAA) ( Zhou et al, 2020 ), GSCs ( Fang et al, 2017 ), and hepatocellular carcinoma (HCC) ( Huang et al, 2020 ). Consistently, knockdown or pharmacological inhibition of USP13 antagonized tumor cell growth.…”
Section: Cellular Function Of Usp13mentioning
confidence: 99%
“…For example, in non-small-cell lung cancer, downregulation of USP13 suppresses ATK/MAPK signaling, reducing c-Myc protein levels and retards tumor growth both in tumor cells and nude mice ( Wu et al, 2019 ). In cholangiocarcinoma, TGF-β signaling triggers the phosphorylation of CLK3, a serine/threonine kinase that directly phosphorylates USP13 at Y708 and facilitates USP13 interaction with c-Myc ( Zhou et al, 2020 ); in GSCs, USP13 can enhance the stability through deubiquitinating c-Myc, activating purine synthesis mediated by c-Myc and inducing the tumorigenesis of GSCs ( Fang et al, 2017 ); in hepatocellular carcinoma, knockdown of USP13 by shRNA can markedly downregulate c-Myc expression, resisting xenograft tumor growth of HCC ( Huang et al, 2020 ). Hence, inhibition of USP13 might be beneficial for related cancer treatment.…”
Section: Cellular Function Of Usp13mentioning
confidence: 99%